How A Coffee Shop Increases The Welfare Of Societies Through Ecosystem Orchestration: A Dynamic Capabilities Perspective - Anjar Priyono; Syadiyah Abdul Shukor; Abdul Moin; Norasikin Salikin (Bussecon International Academy, 2026)
Non-Indexed Publication